Termination sequence between an inducible promoter and ubiquitous chromatin opening element (UCOE) reduces gene expression leakage and silencing - Tomoki Yanagi; Shean Fu Phen; Jonah Ayala; Deniz Ece Aydin; Susanna Jaramillo; David M. Truong (Journal of Biological Engineering)
Abstract Background Inducible gene expression circuits enable precise control over target gene activation and are widely used in direct reprogramming. However, their usability is often compromised by DNA methylation-induced silencing, especially in iPSCs. This deactivates genetic circuits in engineered iPSCs preventing them from being used for long-term scalable expansion of desired cell types. A2-ubiquitous chromatin opening elements (A2UCOE) have been recognized for their anti-silencing properties, but they have not been used in human iPSCs with inducible systems for direct reprogramming. This study investigates the role of A2UCOE in inducible systems and identifies strategies to eliminate associated gene leakage enabling long-term use of engineered human iPSCs. Results We developed a compact all-in-one gene circuit — containing a doxycycline-inducible Tet-On system, 863 bp of A2UCOE, and FOXN1, a transcription factor critical for thymic epithelial cell (TEC) differentiation — easily deployed to new genomic sites. However, we observed significant FOXN1 gene leakage even without doxycycline, which is a novel limitation of A2UCOE. This leakage resulted in premature differentiation of iPSCs into TECs, limiting its continued use. To further investigate the relationship between A2UCOE and gene leakage, we generated A2UCOE fragments of varying lengths (1337 bp, 749 bp, and 547 bp) and found that all fragments, regardless of length, caused significant gene leakage. To solve this issue, we tested different spacer sequences between A2UCOE and the inducible promoter and found that the SV40 poly-A terminator fully eliminated FOXN1 leakage, and we show this effect is not due to AT- or GC-content. Unexpectedly, this architecture further enhanced anti-silencing effects > 60% providing prolonged stability for at least 30 days. Conclusions This study reveals a novel limitation of A2UCOE in inducible systems, specifically its contribution to gene leakage, which compromise sensitive systems like direct reprogramming of iPSCs. The inclusion of an SV40 poly-A sequence provides a practical solution and genomic architecture to improve the functionality of A2UCOE-based circuits. It also suggests investigating how termination of transcription modulates gene silencing as a novel design parameter. These findings have significant implications for the design of robust gene circuits, particularly in applications involving iPSCs, regenerative medicine, and cell therapy. Graphical abstract